Land Use changes in Western Ljutomersko-Ormoške gorice in the period 2000–2018 in relation to selected physical geographical characteristics - Slavič, Jakob (Journal for Geography, 2021)
Land Use changes in Western Ljutomersko-Ormoške gorice in the period 2000–2018 in relation to selected physical geographical characteristicsWe can divide the region Ljutomersko-ormoške gorice on Western and Eastern part. Following,are well known by their quality wines, tourism and cultural center Jeruzalem. On the other hand,Western Ljutomersko–Ormoške gorice are hiding in the shadows of the Eastern part. That’s why the process of farm dropping, migration of youth, urbanisation has changed the area of Western Ljutomersko-Ormoških goric, even more. With this kind of movement in the area,Land use has changed a lot. The number of overgrow lands, forest lands, green lands and none arable areas has increased. This kind of land use, can follow to physical geographic changes of areas, as well as to culture changes of areas. The biggest problem of changes in land use are unsensibly use of land. Mostly by overlaying of none arable areas with arable areas, where there are good farming areas.